2016
DOI: 10.1155/2016/6940283
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cells Applications in Regenerative Medicine and Disease Therapeutics

Abstract: Regenerative medicine, the most recent and emerging branch of medical science, deals with functional restoration of tissues or organs for the patient suffering from severe injuries or chronic disease. The spectacular progress in the field of stem cell research has laid the foundation for cell based therapies of disease which cannot be cured by conventional medicines. The indefinite self-renewal and potential to differentiate into other types of cells represent stem cells as frontiers of regenerative medicine. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
318
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 470 publications
(321 citation statements)
references
References 125 publications
1
318
0
2
Order By: Relevance
“…Fortuitously, innovations in intestinal stem-cell culture methods have made it possible to use primary, non-transformed cells to create specialized tissues in vitro [34, 35]. With these methods, primary animal and human intestinal stem cells can be used to create multi-cellular structures known as enteroids that mimic many of the aspects of the small intestinal epithelium [11, 36].…”
Section: Introductionmentioning
confidence: 99%
“…Fortuitously, innovations in intestinal stem-cell culture methods have made it possible to use primary, non-transformed cells to create specialized tissues in vitro [34, 35]. With these methods, primary animal and human intestinal stem cells can be used to create multi-cellular structures known as enteroids that mimic many of the aspects of the small intestinal epithelium [11, 36].…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) are multipotent cells that are isolated from many adult tissues such as adipose, bone marrow, muscle, and umbilical blood. MSCs can be differentiated into mesoderm lineages, namely, adipocytes, osteoblasts, and chondrocytes . Furthermore, it has been shown that MSCs have the potential to differentiate into cardiomyocytes, myocytes, hepatocytes, and neural cells.…”
Section: Introductionmentioning
confidence: 99%
“…Stem cells are the “master cells” of tissues and organs of the body, which undergo differentiation to serve mainly for restoration or replacement of worn out, injured, or diseased cells of various tissues and organs , such as heart, bone marrow, brain, muscle tissues, skin, and so on, and have been adapted for their regenerative roles . There are two major types of stem cell in mammals: embryonic stem cells (ESC) which are somatic cells capable of differentiating to become part of all cell types found in tissues and organs of the body such as heart, nervous, immune system, etc, therefore, have been termed is pluripotent . ESC originates from the inner mass cells of a blastocyst .…”
Section: Dimensional Stem Cell Culturementioning
confidence: 99%